Tuberculoma Brain and its Early Radiological Presentation; Descriptive Analytical Study - Shahzad, Ghazala; Nayab, Seema; Shaikh, Ashfa Hassan; ., Anam (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To highlight the radiological presentation of tuberculoma brain in association with clinical features of the disease METHODOLOGY: As Descriptive analytical nature of study, it was held in Radiology Department of liaquat University Hospital Hyderabad from June 2018 to December 2018. The cases were referred from medicine and neurosurgery ward to the radiology department for MRI and CT scans. The fillings of questionnaire and co relation of its radiological findings with clinical aspect were examined by evaluating patients file and diagnosed on clinical suspicion, CSF findings, improvement on empirical treatment, diagnosis of exclusion and multi discipline discussion. RESULTS: Total numbers of 20 patients were included, mostly younger age were affected with male preponderance. Mostly cases were presented with meningitis (80%), seizures (60%) and history of tuberculosis (60%). On CT and MRI brain scan, the most common findings were multiple lesions (95%) showed central hyper-intensity on T2 (55%) with meningeal enhancement (80%), fluid- attenuate inversion recovery (FLAIR) signals (35%) and hypo-intense core with hyper-intense rim (30%) reflecting the most of cases with early non caseating nature of tuberculoma. Ring like lesions (80%) and irregular shape (45%) with (25%) target like lesions were found and associated with edema (55%) and calcifications (10%). CONCLUSION: The presentation of tuberculoma is no more a rare manifestation of infective CNS disease. Early identification on scans with characteristics of early non caseating granuloma can help in prompt diagnosis and treatment which in turn decreased the disabling nature of disease and its progression.